2019
DOI: 10.32615/ps.2019.122
|View full text |Cite
|
Sign up to set email alerts
|

Factors playing role in heat acclimation processes in barley and oat plants

Abstract: In the present study, the heat acclimation processes (growing at 30/27°C for 2 weeks) in spring and winter varieties of barley (Hordeum vulgare L., varieties 'Conchita' and 'Mv Initium') and oat (Avena sativa L., varieties 'Mv Pehely' and 'Mv Hópehely') were characterized. Temperature dependence of certain chlorophyll a fluorescence induction parameters indicated the efficiency of heat acclimation. Heat treatment induced the activity of glutathinone-S-transferase, but decreased the amounts of the major polyami… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(13 citation statements)
references
References 47 publications
2
11
0
Order By: Relevance
“…In the next part of the experiments two selected barley (the winter type Mv Initium and the spring type Conchita) and two oat varieties (winter type Mv Hópehely and spring type Mv Pehely), which have been investigated in one of our earlier studies (Darkó et al 2019), were further investigated. A non‐targeted metabolomic analysis focusing on polar metabolite identification and quantitation revealed substantial differences between these species and the primed and non‐primed plants.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…In the next part of the experiments two selected barley (the winter type Mv Initium and the spring type Conchita) and two oat varieties (winter type Mv Hópehely and spring type Mv Pehely), which have been investigated in one of our earlier studies (Darkó et al 2019), were further investigated. A non‐targeted metabolomic analysis focusing on polar metabolite identification and quantitation revealed substantial differences between these species and the primed and non‐primed plants.…”
Section: Resultsmentioning
confidence: 99%
“…However, direct relationship between heat tolerance of the varieties and the changes in the critical temperature values could not be detected in wheat plants. In another study, where different barley and oat genotypes were compared, results suggested that the temperature dependence could differ in spring and winter varieties of these species (Darkó et al 2019). However, since that result was only obtained using 1–1 spring and winter genotypes in both species, a confirmation was necessary in order to generalise the differences between the spring and winter varieties.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations